1998
DOI: 10.1007/s002689900459
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia following Thyroid Surgery: Incidence and Prediction of Outcome

Abstract: Postoperative hypocalcemia is a common and most often transient event after extensive thyroid surgery. It may reveal iatrogenic injury to the parathyroid glands and permanent hypoparathyroidism. We prospectively evaluated the incidence of hypocalcemia and permanent hypoparathyroidism following total or subtotal thyroidectomy in 1071 consecutive patients operated during 1990-1991. We then determined in a cross-sectional study which early clinical and biochemical characteristics of patients experiencing postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
425
4
30

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 503 publications
(496 citation statements)
references
References 16 publications
(22 reference statements)
25
425
4
30
Order By: Relevance
“…Similar to other studies, we did not find a relationship between patient demographic characteristics and development of hypocalcemia (15,(18)(19)(20)(27)(28)(29), and although several authors have reported a relationship between hyperthyroidism and hypocalemia (1,7,28), our study (like those of Lombardi and cols. (29), Higgins and cols.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similar to other studies, we did not find a relationship between patient demographic characteristics and development of hypocalcemia (15,(18)(19)(20)(27)(28)(29), and although several authors have reported a relationship between hyperthyroidism and hypocalemia (1,7,28), our study (like those of Lombardi and cols. (29), Higgins and cols.…”
Section: Discussionsupporting
confidence: 75%
“…We used only the symptoms of hypocalcemia because we believe that mixing two parameters (biochemical hypocalcemia and symptomatic hypocalcemia) can introduce a bias. Postoperative serum calcium level can take up to four days to reach its lowest value (20) and, like Richards and cols., we also found that almost all patients have calcium levels below reference range after total thyroidectomy (27). Furthermore, the speed of decrease in calcium levels appears to be more important that the absolute value itself (4,20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most patients, reductions in total calcium and iPTH were found to be secondary to the impairment of parathyroid function. 8,[21][22][23] Several days after surgery, serum calcium and iPTH concentrations began to recover in parallel. Prophylactic supplementation with calcium and vitamin D contributed to preventing the initial drop in serum calcium levels as well as to preventing the subsequent development of major hypocalcemic symptoms after total thyroidectomy and CND.…”
Section: Discussionmentioning
confidence: 99%
“…Patients must undergo close postoperative observation and laboratory evaluations. The reasons for postoperative hypoparatyroidism that leads to hypocalcemia are injury or devascularisation of a parathyroid gland, accidental removal of 1 or more parathyroid glands, hematoma formations (3,4,5,6). Hospital stay must be often extended due to this complication (7,8).…”
mentioning
confidence: 99%